The 5-Phosphatase SHIP2 Promotes Neutrophil Chemotaxis and Recruitment - Michael, Melina; McCormick, Barry; Anderson, Karen E.; Karmakar, Utsa; Vermeren, Matthieu; Schurmans, Stéphane; Amour, Augustin; Vermeren, Sonja (Frontiers in Immunology, 2021)
Neutrophils, the most abundant circulating leukocytes in humans have key roles in host defence and in the inflammatory response. Agonist-activated phosphoinositide 3-kinases (PI3Ks) are important regulators of many facets of neutrophil biology. PIP3 is subject to dephosphorylation by several 5’ phosphatases, including SHIP family phosphatases, which convert the PI3K product and lipid second messenger phosphatidylinositol 3,4,5-trisphosphate (PIP3) into PI(3,4)P2, a lipid second messenger in its own right. In addition to the leukocyte restricted SHIP1, neutrophils express the ubiquitous SHIP2. This study analysed mice and isolated neutrophils carrying a catalytically inactive SHIP2, identifying an important regulatory function in neutrophil chemotaxis and directionality in vitro and in neutrophil recruitment to sites of sterile inflammation in vivo, in the absence of major defects of any other neutrophil functions analysed, including, phagocytosis and the formation of reactive oxygen species. Mechanistically, this is explained by a subtle effect on global 3-phosphorylated phosphoinositide species. This work identifies a non-redundant role for the hitherto overlooked SHIP2 in the regulation of neutrophils, and specifically, neutrophil chemotaxis/trafficking. It completes an emerging wider understanding of the complexity of PI3K signalling in the neutrophil, and the roles played by individual kinases and phosphatases within.